Unveiling the atomic structure and electronic properties of atomically thin boron sheets on an Ag(111) surface. Issue 36 (26th August 2016) - Shu, Haibo; Li, Feng; Liang, Pei; Chen, Xiaoshuang
Abstract : There exist three stable structures of atomically thin boron sheets (β5, χ1 and χ2 ) on the Ag(111) substrate during the growth, and the simulated STM images are in good agreement with the experimental results. Abstract : Two-dimensional (2D) boron sheets ( i.e., borophene) have a huge potential as a basic building block in nanoelectronics and optoelectronics; such a situation is greatly promoted by recent experiments on fabrication of borophene on silver substrates. However, the fundamental atomic structure of borophene on the Ag substrate is still under debate, which greatly impedes further exploration of its properties. Herein, the atomic structure and electronic properties of borophene on an Ag(111) surface have been studied using first-principles calculations and ab initio molecular dynamics simulations. Our results reveal that there exist three energetically favorable borophene structures (β5, χ1, and χ2 ) on the Ag(111) surface and their simulated STM images are in good agreement with experimental results, suggesting the coexistence of boron phases during the growth. All these stable borophene structures have a planar structure with slight surface buckling (∼0.15 Å) and relatively high hexagonal vacancy density (1/6 and 1/5) and exhibit typical metallic conductivity. These findings not only can be applied to solve the experimental controversies about the atomic structure of borophene on the Ag substrate but also provide a theoretical basis for exploring the fundamental properties and applications of 2D boron sheets.